Second-Order Linear Differential Equations with Solutions in Analytic Function Spaces - Jianren Long; Yu Sun; Shimei Zhang; Guangming Hu (Journal of Function Spaces, 2019)
This research is concerned with second-order linear differential equation f′′+A(z)f=0, where A(z) is an analytic function in the unit disc. On the one hand, some sufficient conditions for the solutions to be in α-Bloch (little α-Bloch) space are found by using exponential type weighted Bergman reproducing kernel formula. On the other hand, we find also some sufficient conditions for the solutions to be in analytic Morrey (little analytic Morrey) space by using the representation formula.